Determinan Loyalitas Nasabah Bank Mandiri: Analisis Kualitas Layanan, Kepercayaan, Dan E-Banking Melalui Kepuasan Nasabah Di Balikpapan - Afrisal Arianto; Fransisca Ursila Y L Y; Wiwin Pebriana; Amran Wahyudiah; Syahril Hasan (Jurnal Ragam Pengabdian, 2026)
This study was conducted to analyze the influence of service quality, customer trust, mobile banking, and customer satisfaction on customer loyalty at Bank Mandiri in Balikpapan City. The approach used in this study was quantitative with a purposive sampling technique for 70 respondents. Data processing was carried out using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS) through the SmartPLS application. The results of the study indicate that customer trust has a positive and significant effect on customer satisfaction. On the other hand, service quality and mobile banking have not been able to provide a significant influence on customer satisfaction or loyalty. Furthermore, customer satisfaction has not been proven to significantly influence customer loyalty. The findings of this study indicate that in the development of digital banking services, the trust factor has become a more dominant aspect in shaping customer satisfaction compared to service quality or mobile banking usage. Therefore, banks need to improve system security, service consistency, and information transparency to maintain customer satisfaction and loyalty.